PENGEMBANGAN MEDIA SMART BOX UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATERI ENERGI KELAS IV SD NEGERI KANGKUNG 3 - Ufera Irba Wiami; Sari Yustiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop Smart Box learning media for energy materials and analyze the level of feasibility, practicality and effectiveness in improving learning outcomes in improving students' critical thinking. This research uses the Research and Development (R&D) method with stages including needs analysis, media design, development, expert validation, and trials. The subjects of the study were students with a total of 25 students. The data research instruments used include expert validation sheets, teacher and student questionnaires as well as tests in the form of posttests. The results of the study showed that Smart Box media obtained a validation score of 0.875 with the category